Integration of Pluralism Values in Civics Learning to Form a Tolerant Attitude in Grade 4 Students of MI Ma'arif Nu Sunan Drajat Lamongan: Integrasi Nilai-Nilai Pluralisme Dalam Pembelajaran PKN Untuk Membentuk Sikap Toleransi Siswa Kelas 4 Mi Ma’arif Nu Sunan Drajat Lamongan - Lestari, Puji; Habibah, Sulhatul; Munif, Moh. Vito Miftahul (Academia Open, 2026)
General Background Civic education plays a strategic role in managing social diversity and developing tolerant character among elementary school students. Specific Background In PPKn learning, pluralism values are integrated to address the gap between students’ conceptual understanding of tolerance and their daily social practices, including sociolinguistic conflict and exclusive peer grouping. Knowledge Gap Previous studies have largely emphasized formal curriculum and teaching materials, while limited attention has been given to classroom management, hidden curriculum, social interaction, and inclusive school culture as contextual spaces for internalizing pluralism. Aims This study aims to analyze the strategic integration of pluralism values in PPKn learning and its implications for forming students’ tolerance. Results The findings show that pluralism values were integrated through contextual learning, heterogeneous group discussion, teacher role modelling, sociopedagogical mediation, inclusive school culture, and school family synergy. These strategies encouraged openness, respect for differences, reduced sociolinguistic conflict, and strengthened consistent tolerant behavior inside and outside school. Novelty This study positions students’ social experiences and hidden curriculum as central mechanisms for pluralism internalization, rather than treating tolerance education only as formal knowledge transfer. Implications The findings provide practical direction for teachers, schools, and parents in developing inclusive civic learning that supports democratic, respectful, and socially aware student character. Highlights • Pluralism values were practiced through contextual learning and heterogeneous interaction.• Teacher mediation reduced sociolinguistic conflict among elementary students.• School family synergy strengthened consistent tolerant behavior beyond classroom settings. Keywords Pluralism; Civic Education; Tolerance; Hidden Curriculum; Inclusive Learning